Revisiting Vitis vinifera Subtilase Gene Family: A Possible Role in Grapevine Resistance against Plasmopara viticola - Figueiredo, Joana; Costa, Gonçalo J.; Maia, Marisa; Paulo, Octávio S.; Malhó, Rui; Sousa Silva, Marta; Figueiredo, Andreia (Frontiers in Plant Science, 2016)
Subtilisin-like proteases, also known as subtilases, are a very diverse family of serine peptidases present in many organisms. In grapevine, there are hints of the involvement of subtilases in defense mechanisms, but their role is not yet understood. The first characterization of the subtilase gene family was performed in 2014. However, simultaneously, the grapevine genome was re-annotated and several sequences were re-annotated or retrieved. We have performed a re-characterization of this family in grapevine and identified 82 genes coding for 97 putative proteins, as result of alternative splicing. All the subtilases identified present the characteristic S8 peptidase domain and the majority of them also have a pro-domain I9 inhibitor, a protease-associated (PA) domain, and a signal peptide for targeting to the secretory pathway. Phylogenetic studies revealed six subtilase groups denominated VvSBT1 to VvSBT6. As several evidences have highlighted the participation of plant subtilases in response to biotic stimulus, we have investigated subtilase participation in grapevine resistance to Plasmopara viticola, the causative agent of downy mildew. Fourteen grapevine subtilases presenting either high homology to P69C from tomato, SBT3.3 from Arabidopsis thaliana or located near the Resistance to P. viticola (RPV) locus were selected. Expression studies were conducted in the grapevine-P. viticola pathosystem with resistant and susceptible cultivars. Our results may indicate that some of grapevine subtilisins are potentially participating in the defense response against this biotrophic oomycete.